Boost dynamic protocols for producing mammalian biopharmaceuticals with intensified DoE—a practical guide to analyses with OLS and hybrid modeling - Nold, V.; Junghans, L.; Bayer, B.; Bisgen, L.; Duerkop, M.; Drerup, R.; Presser, B.; Schwab, T.; Bluhmki, E.; Wieschalka, S.; Knapp, B. (Frontiers in Chemical Engineering, 2023)
For the implementation of robust bioprocesses, understanding of temporal cell behaviour within the growth and production phase with respect to relevant inputs is crucial. Intensified Design of Experiments (iDoE) is an efficient tool to assess the joint influence of input factors by including intra-experimental changes. We applied iDoE to the production phase of a monoclonal antibody in mammalian cells. The multidimensional design space spanned by temperature, dissolved oxygen (DO), timing of change, and growth category was investigated in 12 cultivations. We built both, ordinary least squares (OLS) and hybrid models (HM), on the iDoE-data, validated them with classical DoE (cDoE)-derived data, and used the models as in silico representation for process optimization. The results show iDoE is valid to better understand the mammalian biopharmaceutical production phase if the complexity of the inputs and their interactions is sufficiently captured during planning and modeling. For local behaviour and flexible compositions of desirability functions during optimization, OLS regressions can easily be implemented. To predict global and interconnected dynamics while incorporating mass balances, HM holds potential. iDoE will boost protocols that optimize inputs for each bioprocess phase. The described key aspects of OLS- and HM-based analyses of iDoE-data shall guide future applications during manufacturing.